2013
DOI: 10.1021/jf4005725
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of Metals within Brassica chinensis L. in Response to Elevated Lead and Chromium Stress

Abstract: Differential centrifugation and synchrotron radiation X-ray fluorescence spectroscopy (SRXRF) microprobe were used to study the distribution of the elements in tissue cross sections of pakchoi ( Brassica chinensis L.) under stress of elevated Pb and Cr. Subcellular fractionation of the different tissues grown in a nutrient solution containing 200 mg L(-1) Pb or 5 mg L(-1) Cr showed that 86.7 and 76.3% of the Pb that accumulated in the roots and shoots, respectively, was contained in the cell wall and vacuoles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 46 publications
3
27
0
1
Order By: Relevance
“…The results of this study also showed that all the examined heavy metals especially Cr and Ni accumulated in higher amounts in the roots than in the above-ground parts of a plant. These results agree with results of other authors who examined this issue (Adki et al, 2013;Wu et al, 2013). Gomes et al (2017) reported that plants possess several different strategies to neutralize the negative impact of heavy metals on plants.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study also showed that all the examined heavy metals especially Cr and Ni accumulated in higher amounts in the roots than in the above-ground parts of a plant. These results agree with results of other authors who examined this issue (Adki et al, 2013;Wu et al, 2013). Gomes et al (2017) reported that plants possess several different strategies to neutralize the negative impact of heavy metals on plants.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study strongly corroborate previous finding from Cr hyperaccumulator Leersia hexandra , 83.2% of the root Cr was localized in the cell wall fraction 88 . Researches have also shown that other heavy metals are dealt with in similar ways; Pb was accumulated predominantly in the cell walls of roots in the vegetable pakchoi 89 , while Cd was found principally in the cell wall of shoots in Impatiens walleriana 90 .…”
Section: Discussionmentioning
confidence: 97%
“…Several physiological studies pointed out the role of PCs in the homeostasis and detoxification of Cr and other metals in plants (Shanker et al 2005;Singh et al 2013). Plant removes the toxic effect of Cr by reducing Cr (VI) to Cr (III), followed by complexation of Cr (III) with PC and then this PC-Cr complexes transported to vacuoles (Wu et al 2013). In addition to PC, metallothioneins (MTs), cysteine-rich low molecular weight proteins, also act in Cr detoxification in plants (Shanker et al 2004;Panda and Choudhury 2005).…”
Section: Introductionmentioning
confidence: 99%